Rhoifolin ameliorates titanium particle‐stimulated osteolysis and attenuates osteoclastogenesis via RANKL‐induced NF‐κB and MAPK pathways. Issue 10 (10th March 2019) - Liao, Shijie; Song, Fangmin; Feng, Wenyu; Ding, Xiaofei; Yao, Jun; Song, Huijie; Liu, Yun; Ma, Shiting; Wang, Ziyi; Lin, Xixi; Xu, Jiake; Zhao, Jinmin; et al.
Abstract: Prosthesis loosening is a highly troublesome clinical problem following total joint arthroplasty. Wear‐particle‐induced osteoclastogenesis has been shown to be the primary cause of periprosthetic osteolysis that eventually leads to aseptic prosthesis loosening. Therefore, inhibiting osteoclastogenesis is a promising strategy to control periprosthetic osteolysis. The possible mechanism of action of rhoifolin on osteoclastogenesis and titanium particle‐induced calvarial osteolysis was examined in this study. The in vitro study showed that rhoifolin could strongly suppress the receptor activators of nuclear factor‐κB (NF‐κB) ligand‐stimulated osteoclastogenesis, hydroxyapatite resorption, F‐actin formation, and the gene expression of osteoclast‐related genes. Western blot analysis illustrated that rhoifolin could attenuate the NF‐κB and mitogen‐activated protein kinase pathways, and the expression of transcriptional factors nuclear factor of activated T cells 1 (NFATc1) and c‐Fos. Further studies indicated that rhoifolin inhibited p65 translocation to the nucleus and the activity of NFATc1 and NF‐κB rhoifolin could decrease the number of tartrate‐resistant acid phosphate‐positive osteoclasts and titanium particle‐induced C57 mouse calvarial bone loss in vivo. In conclusion, our results suggest that rhoifolin can ameliorate the osteoclasts‐stimulated osteolysis, and may be a potential agent for the treatment of prosthesis loosening. Abstract : This is a valuable study. Our current study indicates that rhoifolin attenuates receptor activators of nuclear factor‐κΒ (NF‐κB) ligand‐stimulated osteoclastogenesis and osteoclast function by suppressing the action of the NF‐κB and mitogen‐activated protein kinase (MAPK) pathways. Simultaneously, rhoifolin also protects against particle‐stimulated osteolysis in vivo, in concordance with its in vitro effects. Therefore, rhoifolin is a potential therapeutic choice against osteoclast‐related peri‐implant osteolysis.